nüstyle – a neo-generative fashion lifestyle center facilitating circular economy and eco-consciousness in the fashion industry - Dy, Mariella Bernice de Cadiz; Sicam, Olivia Alma G. (Quezon City College of Architecture, University of the Philippines Diliman, 2024)
The fashion industry is the second most polluting and energy-intensive sector,
generating 92 tons of textile waste annually due to fast-fashion’s linear economy and
its throwaway culture. While slow fashion offers more eco-friendly alternatives with its
circular economy model which emphasizes a closed-loop system that extends the
garment's lifecycle, reducing waste and promoting sustainability. Despite this, there is
an evident gap in the knowledge and awareness of consumers, fashion designers, and
manufacturers on which sustainable strategies are the most effective; impeding them
from developing their eco-consciousness. While others are unable to transition due to
the lack of resources. Hence, the lack of consumer, designer, and manufacturer
awareness, as well as the fragmented nature of the industry, hinders the progress of
sustainability initiatives.
This study aims to bridge the gap between these issues by employing a systems thinking
approach to analyze the linear and circular fashion systems and their relationships. By
utilizing interviews, observations, and precedents as references to create an inclusive
fashion lifestyle center rooted in a circular economy, equipped with resources that
enable the pursuit of reuse and repurposing of clothing, in turn promoting
eco-conscious decision-making amongst its constituents. This highlights the importance
of spatial design and organization as tools to create efficient and immersive spaces that
will catalyze the transition towards a more sustainable fashion industry.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Clothing trade; Circular economy; Sustainable consumption